Analisis Kritis Kebijakan Standar Kompetensi Lulusan (SKL) Dan Standar Isi Kurikulum Pendidikan Agama Islam - Abdul Muis Pawero (Journal of Islamic Education Policy, 2017)
Abstract. In the Sisdiknas Law no. 20. Year 2003 in chapter 1 article 3 has been declared that the national education function to develop the ability and form the character and civilization of a dignified nation in order to educate the nation's life, aims for the development of potential learners to be a human being who believes and cautious to God Almighty, be noble, healthy, knowledgeable, capable, creative, independent, and become a democratic and responsible citizen.The purpose of the national education is inversely proportional to the results of a survey that shows that Indonesia country is still perched in the ranks of the most corrupt countries in the world, corruption in various institutions, increasingly loose discipline of increasing violent criminal acts, anarchism, thuggery, alcoholism and drugs struck among the pelajra and students. This paper will discuss the contents of the curriculum and the Competence Standards of Graduation (SKL) of Islamic education to see whether the contents or curriculum materials now meet the expectations or not. So it is necessary to conduct a critical analysis / analysis of the causes of the weak point of Islamic religious education, especially on the content of curriculum materials of Islamic educationKeyword; Policy Analysis, Graduate Competency Standards, Curriculum Content Standards.Abstrak. Dalam Undang-Undang Sisdiknas no. 20. Tahun 2003 pada bab 1 pasal 3 telah dinyatakan bahwa pendidikan nasional berfungsi mengembangkan kemampuan dan membentuk watak serta peradaban bangsa yang bermartabat dalam rangka mencerdaskan kehidupan bangsa, bertujuan untuk berkembangnya potensi peserta didik agar menjadi manusia yang beriman dan bertakwa kepada Tuhan yang maha Esa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab.Tujuan pendidikan nasional tersebut berbanding terbalik dengan Hasil survei yang menunjukkan bahwa negeri kita masih bertengger dalam jajaran negara yang paling korup di dunia, KKN melanda di berbagai institusi, disiplin makin longgar semakin meningkatnya tindak kriminal kekerasan, anarkisme, premanisme, konsumsi minuman keras dan narkoba sudah melanda di kalangan pelajra dan mahasiswa.Makalah ini akan mendiskusikan isi kurikulum serta Standar Kompetensi Kelulusan (SKL) pendidikan agama Islam guna meneropong apakah isi atau materi kurikulum saat ini sudah memenuhi harapan atau belum. Maka perlu kiranya melakukan telaah/analisis secara kritis mengenai penyebab titik lemah dari pendidikan agama Islam terutama pada isi materi kurikulum pendidikan agama Islam.Kata Kunci: Analisis Kebijakan, Standar Kompetensi Lulusan, Standar Isi Kurikulum.